Reproduction de l'huître creuse dans le bassin d'Arcachon, Année 2006 - Auby, Isabelle; Maurer, Daniele; Cassam Chenai, Yoann; Tournaire, Marie-pierre; Neaud-masson, Nadine; Rumebe, Myriam; Cantin, Christian; Debort, Henriette; Germain, Jean-marie; Navarro, Romuald (2006)
Introduction: During each summer season, the IFREMER laboratory of Arcachon monitors, within the framework of the agreement with the Arcachon- Aquitaine Shellfish Farming Regional Section (SRC), the reproduction of cup oysters in the Arcachon basin. This monitoring has as its goal to furnish oyster farmers with the information needed to implement spat catches: - dates and size of egg clutches, - larvae development rate, - presence in the environment of more evolved stages (close to fixation). Reproduction was monitored between mid-June and mid-September, plankton was fished four times per week at the various sites representative of the basin. Oyster larvae at various stages are enumerated there. At the end of the reproductive season (September to October), the assessment of larvae recruitment on the collectors is made by counting the spat captured over a certain number of sampled tiles, with the help of the office of Maritime Affaires of Arcachon, in the various catch sectors. Moreover, the results obtained in the context of the REMORA network (IFREMER's National Mollusc Network) are used to characterise the genitors' maturation during the spring that precedes the reproductive season. This report shows the results of the 2006 reproductive season, interpreted in light of the recent summary of the series of old data (Auby et al., 2000 2002a Maurer et al., 2001, 2003 Auby et Maurer, 2004). Introduction : Durant chaque saison estivale, le laboratoire IFREMER d'Arcachon réalise, dans le cadre d'une convention avec la Section Régionale Conchylicole (SRC) Arcachon- Aquitaine, le suivi de la reproduction des huîtres creuses dans le Bassin d'Arcachon. Ce suivi a pour but de fournir aux ostréiculteurs les informations nécessaires à la mise en oeuvre du captage de naissains : - dates et importance des pontes, - vitesse de développement des larves, - présence dans le milieu des stades les plus évolués (proches de la fixation). Le suivi de la reproduction est réalisé entre mi juin et mi septembre, des pêches de ...